The Effectiveness of Sidearm Throw in Softball Players - Irawan, Fajar Awang (Media Ilmu Keolahragaan Indonesia, 2015)
Introduction: The good throws need acceleration, and acceleration starts from maximum lateral rotation with the ball come quickly to the target. The aim of this study was to investigate the comparison between sidearm and overhand throws. Method: 60 players participate in this study (age 20.9±0.4, Height 168.9±5.3, Weight 58.8±5.3 and BMI 20.6±1.8). All participants are beginner and they are right handed. Throw test in this study were sidearm and overhand throws technique with ten meters in one minute. Stopwatch is used to calculate the time for sidearm throw and overhand throw, and Dartfish software version 4.5.2.0 is used to analyze throwing motion. The paired t-test in this study was p < 0.05 to analyze the data. Result: The sidearm and overhand throws had significant differences with the average in one minute was 18.08 times and overhand throw was 15.55 times. Base on the motion analysis view in Dartfish, sidearm throw is simpler and faster, which meant side arm throw was more easy to use than overhand throw by the players. Conclusion: sidearm throw more effective than overhand throw, because the movement is shorter and simpler.